Pedological and agrochemical investigations on media using in vegetable forcing - Jakusné Sári, Sz. (International Journal of Horticultural Science, 2004)
In spite of the several good properties of peat, recently, some experiments were carried out with the aim of finding natural materials which can substitute for peat. According to the results, several inorganic and organic materials were proved to be suitable for this purpose. This study examines the effect of different organic materials (example: pine bark, composts, peats) on the growth and yield of green pepper (Capsicum annuum L., variety Danubia). We found that the most developed plants were grown in peat-mixtures and pine bark. The average fruit weight was the highest at those plants which were planted also in these media. The plants which were grown in composts fell short of our expectations in development and in yield, too.